Research on the Importance of University Design in Promoting Rural Agricultural Product Development (Journal of Global Arts Studies, 2025)
Background: Rural agricultural products need to leverage design to enhance their market competitiveness or brand value. As an important carrier of creative resources, university design is increasingly attracting attention in serving the local economy. Objective: This paper explores the role and value of university design in promoting the development of rural agricultural products, focusing on the integration of rural agricultural and sideline product culture with university specialty programs, so that rural culture and university programs can progress together. Methods: Using the basic concepts of university design and rural agricultural products, this study analyzes the practical foundation for their collaborative development. By examining typical cooperation cases, it reveals the actual effectiveness of university design in product packaging, brand building, and cultural dissemination. Results: University design can effectively enhance the visual recognition of rural agricultural products, promote product differentiation and competition, while also driving the optimization of rural industrial structures and facilitating brand transformation. Conclusion: University design plays an irreplaceable role in promoting the high-quality development of rural agricultural products. It is a key tool for achieving industry-education integration, empowering rural economies, and implementing the rural revitalization strategy, with broad application potential.
Keywords: University Design; Rural Areas; Agricultural Product Development; Importance Research